Development of Powtoon Learning Media in Chemical Bonding Subject for Class X SMA/MA Equivalent Student - Yuhelman, Nofri; Anggraini, Septi; Putri Musdansi, Dwi (Edukimia, 2023)
This research on Powtoon learning media development aims to explain the feasibility of Powtoon media development in chemical bonding subjects for class X SMA/MA equivalent student. This type of research is development (Research and Development, RD) with 4D development models that include the Define (Definition), Design (Design), Development (Development), Disseminate (Deployment) stages. The data collection instruments used are through media expert validation sheets, material expert validation sheets, teacher response sheets and student response sheets. The data analysis technique used is to calculate the judgment percentage score of experts. Research results show that the developed Powtoon learning media met the valid category with presentation of 89,5% from 2 media experts, while that of the 2 material experts received an presentation of 86%. This learning media also met the good categories from 3 teacher response of 87.3% and of 10 students of 87.9%.